The Shift of Tourism Destinations from Bali to Lombok: A Conceptual Analysis of Tourism Security and Competitiveness - Ilhamalimy, Ridho Rafqi; SUHUD, USEP SUHUD; WIBOWO, SETYO FERRY (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2025)
This conceptual study examines the phenomenon of tourist destination shifting from Bali to Lombok with a focus on two main factors: perceived safety and destination competitiveness. Using a descriptive-qualitative approach and a systematic literature review, this study synthesizes theories related to risk perception in tourism and destination competitiveness. The findings show that tourists’ perceptions of safety significantly influence their destination choice decisions, while competitiveness elements such as unique attractions, infrastructure, service quality, and environmental sustainability enhance Lombok’s attractiveness as an alternative to Bali. Lombok’s increased competitiveness and perception as a safer destination contribute to its popularity among tourists seeking post-crisis travel experiences. The conceptual framework developed provides theoretical contributions and practical implications for destination management, emphasizing the importance of an integrated strategy that includes risk management and competitiveness enhancement to attract and retain tourists in a dynamic global tourism environment.